Sentiment Analysis on the Application of Tabungan Perumahan Rakyat (TAPERA) Policy in Indonesia - Dzulfikar, Mochamad Naufal (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Tapera is a program provided by the Indonesian government to provide poor people with decent housing, by charging all working classes with salaries above the Regional Minimum Wage of 3% for Tapera contributions. Even though it seems that this program aims to help poor people, this has given rise to a new polemic, which can be seen from some people who don't like this, as can be seen from several negative comments on social media, one of which is X or Twitter. This paper aims to determine whether public sentiment toward the TAPERA policy is positive or negative among Indonesians affected by it, regardless of whether the sentiment analysis results are predominantly positive or negative. This research is conducted by collecting data from Twitter and then processing it in such a way that, later will be checked for sentiment analysis with the Naive Bayes method. Out of 742 analyzed tweets (filtered from an initial 1,680), 651 expressed negative sentiment, while 91 were positive, indicating significant public dissatisfaction with the TAPERA policy.